Situational analysis of antimicrobial stewardship program (ASP) among public and private sector tertiary care hospitals in Karachi, Pakistan: A qualitative case study - Asma Pethani; Atif Riaz; Shagufta Perveen; Ali Faisal Saleem (Cambridge University Press, 2023)
Abstract Objective: To assess the current status of implementation of the Antimicrobial Stewardship Program (ASP) across Tertiary Care Hospitals in Karachi, Pakistan. Design: Exploratory qualitative case study. Setting: Public and private tertiary care hospitals in Karachi, Pakistan Participants and Methods: The study data were collected from 3 public and 4 private tertiary care hospitals. Twenty-eight in-depth interviews were conducted from the Chief Executive Officer, Chief Medical Officer, Medical Superintendent, and departmental heads of internal medicine, general surgery, and pediatric, respectively. Purposive sampling was done to include higher and middle managers, whereas the infectious diseases consultant, infectious diseases/clinical pharmacist, and clinical microbiologist were interviewed through snowball sampling methodology. Analysis was done using NVivo. Data were source-triangulated within and among the study setting and study participants. Results: We found that more than two-thirds (n = 5, 71%) of tertiary care hospitals in Karachi do not have a structured ASP which includes major public sector hospitals (n = 3, 43%) and half of the private sector hospitals (n = 4, 29%). The study results led to four broad themes, (1) ASP structure, (2) ASP interventions, (3) hospital medical record-keeping system, and (4) structured way for analyzing and reporting mechanism of data related to the ASP. At H1 and H2, there was a consistency in ASP structure and interventions, whereas paucity seen among remaining tertiary care hospitals. Conclusion: There is an alarming need for ASP in the public and private sector hospitals in Karachi. This study can inform future stakeholders regarding ASP and strategies for structural change at hospitals.